2018
DOI: 10.1111/jav.01527
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic species distribution models reveal spatiotemporal habitat shifts in native range‐expanding versus non‐native invasive birds in an urban area

Abstract: Urbanisation as a major driver of changes leads to the extinction of some species while others increase in abundance, especially non‐native species. Spatiotemporal distribution patterns of these successful species are likely to be shaped by their response and tolerance to urban features. This study assesses the anthropo‐ecological requirements of two co‐occurring bird species, the native range‐shifting jackdaw Corvus monedula and the non‐native invasive ring‐necked parakeet Psittacula krameri. We built yearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…, Le Louarn et al. ). Short‐term fluctuations in distribution throughout the annual cycle can be driven by species shifting habitats, tracking ephemeral resources, or migrating between regions (Fahse et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Le Louarn et al. ). Short‐term fluctuations in distribution throughout the annual cycle can be driven by species shifting habitats, tracking ephemeral resources, or migrating between regions (Fahse et al.…”
Section: Introductionmentioning
confidence: 99%
“…Populations are seldom completely static, but are characterized by spatiotemporal dynamics that unfold at a variety of scales. Long-term changes in the distribution of populations may be caused by climate change or land-use change (Massimino et al 2015, Le Louarn et al 2018). Short-term fluctuations in distribution throughout the annual cycle can be driven by species shifting habitats, tracking ephemeral resources, or migrating between regions (Fahse et al 1998, Skagen et al 2005, Runge et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Our linear models also suggested that food provided by urban park visitors is an important factor promoting the establishment of alien populations of Siberian chipmunks, as observed for other naturalized invasive species (e.g. Le Louarn et al ., ; Wauters & Martinoli, ). Considering the experiences from France, where the chipmunk is considered to be responsible for an increased spread of the Lyme disease (Vourc'h et al ., ), food‐provisioning by humans in urban parks should be avoided to limit population growth.…”
Section: Discussionmentioning
confidence: 99%
“…SDMs have also been useful at more local scales to demonstrate that dynamic land use changes in business areas (turnover from brownfield to developed sites and vice versa) has resulted in an increase in biodiversity [76,77] or to demonstrate environmental injustice in a local area, with residents of low to mid income tracts being further away from open spaces and thus exposed to less biodiversity and tree canopy [78]. SDMs helped to predict the habitat shifts of two range-expanding native and non-native species [79] and to produce risk maps for two mosquito species that serve as vectors for dengue fever and West Nile Virus [80]. NbS in cities can provide potential habitats acting as inter-population connectivity corridors, and SDMs can be used to derive fine-scale potential connectivity models which allow the identification of connected and completely isolated populations within a study area to detect small linear structures that are important for the inter-population connectivity of specific species [81].…”
Section: Predicting Where Species Will Bementioning
confidence: 99%